Comparative study of Reynolds number and Flowrate effects on the thermal–hydraulic performance of corrugated channels with winglets using TiO₂ nanofluids - Shadan Kareem Ameen; Adnan Muhammed Hussein (Center of Biomass & Renewable Energy (CBIORE), 2026)
This study aims to provide a deeper and more realistic understanding by conducting a systematic comparison between the two approaches (Reynolds number and volumetric flowrate). The analysis emphasizes the impact of internal channel design, using inclined winglets and surface corrugation. An experimental investigation was carried out to prepare and characterize a TiO₂/H2O nanofluid at 1% volume concentration, including accurate measurements of its thermophysical properties and stability validation. A numerical model was also developed using ANSYS Fluent to simulate the hydrothermal behavior of two channel configurations (straight and corrugated), in which the effects of both Reynolds number and flowrate were evaluated across key parameters such as heat transfer coefficient, pressure drop, performance evaluation criterion, and wall temperature distribution. By observing the flow patterns inside the corrugated channel, three distinct flow behaviors were identified: axial flow along the channel, transverse flow induced by winglets, and swirling flow within the corrugated grooves. This combination of flow modes enhanced fluid mixing and significantly improved heat transfer performance. The results show that TiO₂ nanofluid significantly enhances the thermal–hydraulic performance, with the relative friction factor (Γ) increasing from 6.9 to 7.6 and the thermal enhancement ratio (En) reaching 2.8 (PEC ≈ 1.5) when evaluated using Reynolds number, while volumetric flow rate assessment (7–9 L/min) yielded higher Γ (3.9–4.2) and En/PEC (2.5/1.6). The effects of the internal enhancement techniques were found to be more pronounced when using flowrate as the reference indicator. This work represents a valuable scientific contribution by integrating three advanced enhancement strategies (surface corrugation, inclined winglets, and nanofluid), and it highlights the need to reconsider traditional thermal system design methods based solely on Reynolds number.